A Review of Coal Fly Ash Utilization: Environmental, Energy, and Material Assessment - Monika Kuźnia (Energies)
Global coal consumption is continuously increasing. It is still the primary fuel used in power plants. Despite policies in the European Union aimed at reducing coal consumption, there are countries in the world where coal use continues to rise (China and India are the largest consumers of coal). Coal combustion produces waste, 70% of which is fly ash. It consists mainly of SiO2 and Al2O3. Fly ash also includes Fe2O3, TiO2, MgO, K2O, and CaO. This article describes various methods of using fly ash. Fly ash can be used in the cement industry, as a filler in materials, in zeolite synthesis, in cenosphere separation, in agriculture, in water purification, in road construction as an asphalt filler, and in mine backfilling. An interesting method of using fly ash as a filler in the production of rigid polyurethane foam was also described. The article concerns potential uses in accordance with the principles of a Circular Economy. The environmental, energy, and material aspects are discussed.